Kombinasi Analytical Network Process (ANP) dan Technique For Others Reference by Similarity to Ideal Solution (TOPSIS) untuk Menentukan Penerima Bantuan Rastra - Yunita Yunita; Rusdi Efendi; Evita Hardanita (Program Studi Sistem Informasi, Fakultas Sains dan Teknologi, Universitas Islam Negeri Raden Fatah Palembang, 2021)
The problem of poverty is still a priority for the Indonesian government. The Indonesian government has launched several programs to assist in alleviating poverty, one of which is the rice program for prosperous families, called Rastra. In the implementation of the Rastra program, it should be carried out objectively so that the distribution of the program can be right on target, but there are still problems in determining the recipients and the accuracy of the distribution of Rastra program. This study aims to combine the ANP and TOPSIS methods in helping to provide recommendations for recipients of Rastra program, besides that in this study also measuring the level of accuracy between the implementation carried out with the real data. In this study, a combination of ANP and TOPSIS methods was used in decision making. The ANP method is used to determine the weight of the criteria used, while the TOPSIS method is used to determine the recommendations for recipients of the Rastra program. The accuracy test was carried out in 13 villages in the Gunung Megang, Muara Enim. The results of the tests carried out obtained an average of 84.10%. This shows that the combination of these two methods can be applied as a solution in providing recommendations for recipients of the Rastra program.